DETERMINANTS OF CHOICE OF ASSORTMENT SIZE AT A POINT OF SALE - S. Petrova (Trakia Journal of Sciences)
Retailers today use highly efficient economic tools that enable them to make appropriate decisions about assortment size. The determinants that assist or restrict a retailer’s choice influence largely the overall size of assortment offered. The main purpose of this study is to focus on examining and interpreting basic theoretical-methodological and empirical formulations regarding retailers’ strategic choice of assortment size and, on this basis, to distinguish the economic effects manifested at the point of sale. The scientific methods of theoretical and empirical research that are used involve: factor analysis and synthesis, comparison, generalization, induction and deduction, illustration through figures and tables. The outcomes of the study are summarized in the conclusions drawn and relate to outlining retailers’ preferences regarding the choice of appropriate assortment size.